Weather to scoot? How weather shapes shared e-scooter ridership patterns. (October 2022) - Kimpton, Anthony; Loginova, Julia; Pojani, Dorina; Bean, Richard; Sigler, Thomas; Corcoran, Jonathan
Abstract: Weather, climate, and daily human mobility patterns are inextricably linked, and so quantifying and examining these patterns is essential for smarter urban policy and design that are tailored to support our daily mobility needs and foreground urban sustainability. This study provides an empirical approach to better understanding the interface between weather, climate, and daily human mobility on >800, 000 shared e-Scooter trips across subtropical Brisbane, Australia. We find that the number of eScooter trips increases with heat and declines with rain. However, results reveal that the 'connectivities' between land use types remain stable irrespective of weather conditions while trip distance contracts during inclement weather. As such, weather influences the appeal and distance of eScooter trips but seemingly not trip purpose.